Employee Turnover: Less is Not Necessarily More? - Harris, Mark; Tang, K.; Tseng, Y.-P. (Emerald Group Publishing, 2006)
Theoretical studies have suggested firm specific human capital and job matching as the major, but opposite, mechanisms through which employee turnover affects labour productivity. This study finds that the former dominates when turnover is high, while the latter dominates when turnover is low. The optimal turnover rate that maximises productivity is about 0.22 per annum. Bringing the observed turnover rates in the sample to the optimal level increases the average productivity by 1.1 per cent. The large gap between the observed and the optimal rate could be explained by the lack of decision coordination between agents in labour markets.